1995
DOI: 10.1016/0014-5793(95)00924-x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and partial cloning of ryanodine‐sensitive Ca2+ release channel protein isoforms from human myometrial smooth muscle

Abstract: Partial cDNAs of the ryanodine receptor were cloned using PCR analysis from reverse transcribed total and mRNA, extracted from freshly isolated pregnant, non-pregnant, and cultured human myometrial smooth muscle. The identity of these clones was confirmed by nucleotide sequencing of the fragments and indicate the expression of both the skeletal and brain ryanodine receptor isoforms in these preparations. In freshly isolated non-pregnant myometrial tissue, membrane fractions displaying specific [3H]ryanodine bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
27
2

Year Published

1995
1995
2004
2004

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 39 publications
4
27
2
Order By: Relevance
“…For example, fura-2 and 45 Ca 2ϩ efflux measurements revealed that Ca 2ϩ release from intracellular stores of human uterine smooth muscle cells was ryanodine-sensitive but caffeine-insensitive (62,63). In addition, ryanodine caused an increase in intracellular Ca 2ϩ concentrations in human Jurkat T-lymphocytes that express RyR3, but caffeine did not (64).…”
Section: Discussionmentioning
confidence: 99%
“…For example, fura-2 and 45 Ca 2ϩ efflux measurements revealed that Ca 2ϩ release from intracellular stores of human uterine smooth muscle cells was ryanodine-sensitive but caffeine-insensitive (62,63). In addition, ryanodine caused an increase in intracellular Ca 2ϩ concentrations in human Jurkat T-lymphocytes that express RyR3, but caffeine did not (64).…”
Section: Discussionmentioning
confidence: 99%
“…IP 3 receptor types 1, 2 and 3 are expressed in human myometrium; IP 3 receptor concentration does not change in pregnancy (Rivera et al 1990;Morgan et al 1996). Myometrium also expresses type 2 and type 3 ryanodine receptors (Lynn et al 1995;Martin et al 1999a,b). These receptors are involved in calcium-induced calcium release from intracellular stores and have been suggested by some, but not all, studies to play a role in Ca 2+ i oscillations and general cellular calcium dynamics (Lynn et al 1993;Holda et al 1996;Phillippe & Basa, 1996;Burghardt et al 1999;Fu et al 2000).…”
mentioning
confidence: 99%
“…According to recent reports, at least in some types of smooth muscle cells (SMC), cADPR can elicit the [Ca 2ϩ ] i release (8,9) from sarcoplasmic reticulum and cell contraction (9). As in other muscle cells, the contraction of uterine myometrial smooth muscle cells (SMC) is regulated by increase in cytosolic Ca 2ϩ in part due to intracellular Ca 2ϩ release (10), and RyR was detected in myometrial SMC (11). An archetypal hormone of steroid superfamily, ␤-estradiol (E 2 ), enhances [Ca 2ϩ ] i release-mediated contractility of myometrial SMC in response to several hormones and autacoids (12).…”
mentioning
confidence: 99%